Stability analysis of MHD stagnation-point flow towards a permeable stretching/shrinking sheet in a nanofluid with chemical reactions effect - Fatinnabila Kamal,; Khairy Zaimi,; Anuar Mohd Ishak,; Pop, Ioan (Penerbit Universiti Kebangsaan Malaysia, 2019)
The magnetohydrodynamic (MHD) stagnation-point flow of a nanofluid towards a permeable stretching/shrinking sheet with chemical reaction effect is investigated. The governing nonlinear partial differential equations are transformed into a system of nonlinear ordinary differential equations using a similarity transformation which are then solved numerically using the boundary value problem solver, bvp4c built in Matlab software. The numerical results are obtained for the skin friction coefficient, local Nusselt number, local Sherwood number as well as the velocity, temperature and concentration profiles for some values of the governing parameters, namely suction/injection parameter and chemical reaction parameter. Dual solutions are found to exist for a certain range of the stretching/shrinking parameter. A stability analysis is performed to determine which solutions are stable and physically reliable. It is found that the first solutions are stable and the second solutions are unstable.